E-113 Versatility of the scepter mini low-profile balloon for various endovascular indications. (23rd July 2022) - Orru, E; Patel, N; Marosfoi, M; Wakhloo, A
Abstract : Purpose: Due to size and flexibility constraints, most supercompliant endovascular balloons can only be employed in relatively proximal segments of the vessels of interest, limiting the feasibility of balloon assisted coil embolization or liquid embolic injection. We describe our experience with the Scepter Mini (SM) microballoon in treatment of four different neurovascular diseases. Methods and Supplies: We present technical details and procedural complications of all patients who underwent embolization with the SM. Results: Five procedures were performed with SM assistance over two months: one aneurysm coiling, embolizations of two DAVFs (cervical and posterior fossa) and one large brain AVM, and one preoperative meningioma embolization.In one patient with a small, ruptured, wide-necked pericallosal aneurysm, the SM was placed across the A2 bifurcation (vessel size: 1.3–1.7 mm) and inflated multiple times during coiling, providing excellent neck remodeling with no distal embolization or vascular damage.In one patient with multiple symptomatic cervical DAVFs, the SM was positioned and inflated into a distal thyrocervical trunk feeder (1.2 mm) and Onyx 34 was infused through the second lumen, obviating the need for plug creation and obliterating the target dAVF.A patient with hemorrhage from a posterior fossa DAVF was treated by Onyx injection through a SM inflated very proximally in the posterior meningeal artery. Despite proximal position of the SM due to extreme tortuosity of the vessel, Onyx 18 could reach the fistulous point after balloon inflation, yielding an uncomplicated obliteration of the shunt.Two SMs were used to embolize a large medial frontoparietal AVM with numerous enlarged anterior cerebral artery feeders. An SM was advanced into each pedicle (average 2.3 mm) and inflated prior to infusing Onyx 18 over an average 20 minutes in each feeder, achieving excellent nidal penetration without reflux. The procedure was performed under evoked potential monitoring without complication.In a patient with a large frontal meningioma, the SM was navigated in the main meningeal feeder (1.4 mm). Onyx 18 was infused under balloon inflation with extensive parenchymal penetration and devascularization of 90% of the tumor bed.All SMs were prepared with full contrast for optimal visibility and navigated over a 0.008' Hybrid Microwire with the patient fully heparinized. Navigation was possible in all cases, and no balloon-related vascular injuries occurred. Conclusions: The SM can allow balloon assisted endovascular procedures in very distal territories and in small vessels. Disclosures: E. Orru: None. N. Patel: None. M. Marosfoi: None. A. Wakhloo: 1; C; Philips, Medtronic. 2; C; Stryker, Phenox. 4; C; InNeuroCo, Deinde.